KARAKTERISTIK GAYA KEPEMIMPINAN TERHADAP KINERJA KERJA PEGAWAI KANTOR CAMAT MEUREUBO KABUPATEN ACEH BARAT - Safrianto, Yoyon; Meisartika, Refi (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
This study uses a descriptive method with a qualitative approach. The data source used for this research is field research. Conduct interviews, observations and direct documentation of the object in question, namely the leadership and employees of the Meureubo sub-district office, West Aceh Regency. The results showed that the characteristics of leadership style on the work performance of the employees of the Meureubo sub-district office, West Aceh Regency had a low significant level, meaning that the leadership style in the Meureubo sub-district office did not fully have the characteristics that a leader should have, there is still a high level of egoism towards each leader, leaders do not involve employees in many activities and activities. Therefore, this greatly affects the work performance of employees but is not significant. Simultaneously, the characteristics of leadership style have a negative and insignificant effect on employee work performance. Because, employees do not understand or master the skills according to the portion set. So that it has an impact on the lack of productivity of employees in carrying out their duties, not achieving the goals and expectations that make the assigned tasks not completed and the occurrence of blaming each other between employees. Leaders should give rewards or awards to employees who do their work optimally and have special skills or more who can develop the Vision and Mission of the Meureubo sub-district office. Because the agency should have a leader not only to lead, but to refer the agency to make changes